Urgensi Rekrutmen dan Seleksi Bagi Pelaku Usaha Franchise - Fithri, Windy Dwi Zhelsa; Sofiayen, Sofiayen; Thayib, Thayib (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Recruitment is an initial organisational activity with the aim of identifying and finding potential employees. After the recruitment process, a selection process is needed which is a process to decide on the right employee from a group of prospective employees obtained through the recruitment process, both internal and external recruitment. The recruitment and selection process is a unity process that cannot be separated. The purpose of this study was to determine the recruitment and selection system used by Frozen Food MSMEs (UD Seleraku) by applying the Franchise method. This research is qualitative research using a case study approach. The research was conducted to understand the subject's actions in responding to the franchise phenomenon. Data were obtained through the interview method and supported by scientific papers relevant to the research conducted. The results of this study are that the employee search process for the recruitment process is carried out peer to peer and there are no certain criteria for someone to become a franchisee at UD Seleraku. UD Seleraku also applies 2 sources of selection, namely internal and external. Keywords: Recruitment; Selection; Franchise; MSMEs